Coupling Stability and Multi‐Frequency Transient Characteristics of a Variable Speed Pumped Storage Power Station Under Generating Mode - Rui Cao; Wencheng Guo (Energy Science & Engineering)
ABSTRACT Coupling stability and multi‐frequency transient characteristics of variable speed pumped storage power station (VSPSPS) under generating mode are main topics of this paper. Firstly, the overall model of VSPSPS is established and the coupling stability analysis of VSPSPS is carried out. Then, multi‐frequency transient characteristics of VSPSPS are revealed and the generation mechanism is clarified. Finally, the influence of active power regulation and speed regulation on stability and transient characteristics of VSPSPS is analyzed. The results show that coupling stability of VSPSPS can be characterized by a stable domain determined by the control parameters of the governor. Transient response processes of VSPSPS present multi‐frequency characteristics with three frequencies. The low frequency is dominated by diversion pipeline and surge tank. The high frequency is dominated by pressure pipeline, pump‐turbine and governor. The medium frequency is dominated by doubly‐fed induction motor (DFIM) and frequency converter. Active power regulation has almost no influence on stability of VSPSPS. To suppress the influence of active power regulation on speed regulation, and realize the rapid and high‐quality regulation of active power, it is suggested to select large control parameters of frequency converter. Large operating speed is beneficial to stability. Control parameters of the governor have little effect on active power regulation.